Profesor Kazimierz Nitsch i jego językoznawcze środowisko we wspomnieniach studentki z lat 50. XX w. - Jadwiga Zieniukowa (Ksiegarnia Akademicka Publishing, 2019)
Professor Kazimierz Nitsch and His Linguistic Milieu in the Memories of a Student from 1950s The paper discusses the history of Polish and Slavic linguistics in Poland in the 20th century, with a special regard to dialectology. In the centre of its attention lies the Cracow (Cracow-Lviv) linguistic school of Professor Kazimierz Nitsch. The author describes it primarily on the basis of personal scientific contact (in the middle of the 20th century) with the father of Polish dialectology, Professor K. Nitsch, and a team of researchers from his Department of Atlas and Dictionary of Polish Dialects of the Polish Academy of Sciences (Cracow, Mikołajska street). She looks back at the seminar Nitsch held for researchers, which she attended as a Master’s student at the Jagiellonian University. She presents Professor as a researcher, organizer of team research, academic teacher, as well as a scientific guide, a scholar, and author of linguistic publications in various periods of the 20th century. She draws particular attention to Nitsch’s pioneering works on Kashubian and other Pomeranian dialects. The paper also talks about the long-term radiation of Professor Nitsch’s scientific school, and how his students from various generations – such as Zdzisław Stieber, Nitsch’s student from 1920s, his colleague, and later a creator of a linguistic school himself – as well as students of his students greatly contributed to the advancement of Polish linguistics in the 20th and early 21st century.